ANALYSIS OF LACTIC AND HEMATOCRIT LEVELS OF BLOOD STORAGE IN DR. WAHIDIN SUDIROHUSODO GENERAL HOSPITAL BLOOD BANK - Rysna Wahyu; Asvin Nurulita; Rachmawati Muhidin (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
The components of Packed Red Cells (PRC) are transfused to patients in order to repair oxygen transportation to tissues. The blood is stored at 2-6oC to delay red blood cells metabolism during storage. Red blood cells undergo structural and functional changes biochemically which affect their viability and function. This is a prospective cohort study with time series design. Samples were taken from fresh blood PRC which were moved to transfer bag for approximately 20 mL, then stored in the refrigerator. Lactic acid and hematocrit levels were assessed with spectrophotometry and flow cytometry methods on day 1, day 4, and day 8 of storage in the Dr. Wahidin Sudirohusodo General Hospital Blood Bank. Statistical tests used were Friedman and Wilcoxon. Statistical results are significant if p < 0.05. Total samples were 15 fresh blood PRC. Friedman statistical test showed a significant difference in lactic level (p < 0.001) and hematocrit level (p=0.012) on day 1, day 4, and day 8 of storage. Wilcoxon test showed significantly higher lactic level between day 4 and day 1 (p < 0.01); day 8 and day 1 (p < 0.01); day 4 and day 1 of storage (p < 0.01). Hematocrit level between day 4 and day 1 (p < 0.05); day 8 and day 1 (p < 0.05) were significantly higher; day 8 and day 4 of storage (p > 0.05) showed insignificant difference. Results showed that lactic and hematocrit levels of PRC stored blood were increased according to storage duration. Packed red cells blood is recommended to be given in < 6 days for lower acidosis risk. Further studies are also recommended with a shorter interval of assessment and a bigger sample size.